Esophageal Carcinosarcoma in a Patient with Corrosive Esophagitis - Young Ki Kim; Okran Shin; Sung Soo Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2020)
Esophageal carcinosarcoma is a rare type of esophageal cancer characterized by both carcinomatous and sarcomatous components. Its endophytic growth tendency into the esophageal lumen leads to a higher curative resection rate. However, lymph node metastases in esophageal carcinosarcoma occur at a relatively early stage. We report a case of esophageal carcinosarcoma in a 52-year-old man who had dysphagia for 2 months and a history of ingestion of glacial acetic acid in adolescence. His endoscopy and chest CT results showed an 8.5-cm-sized ulcerative polypoid mass with multiple lymph node metastases in the mid-esophagus. Biopsy revealed an interweaving spindle cell proliferation with squamous dysplasia. Immunohistochemical staining showed positive expressions of vimentin and cytokeratin. Even though the patient received concomitant chemoradiotherapy with a stent insertion, he died 7 months after diagnosis. We herein present a case of corrosive esophagitis followed by esophageal carcinosarcoma that suggested the possibility of an association between the two diseases.